2017
DOI: 10.1097/md.0000000000006775
|View full text |Cite
|
Sign up to set email alerts
|

The role of circulating miR-146a in patients with rheumatoid arthritis treated by Tripterygium wilfordii Hook F

Abstract: Rheumatoid arthritis (RA) is polygenic autoimmune disease with unclear etiology. MicroRNAs (miRNAs) play a critical role in the pathogenesis of RA. The objective of this study was to evaluate the role of miR-146a in patients with RA receiving Tripterygium wilfordii Hook F (TwHF) treatment.In total, 69 patients with RA and 69 healthy controls (HC) were included in the study, and patients with RA received TwHF treatment for 24 weeks. Blood samples were collected from RA patients and HC, and peripheral blood mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Two of these were excluded because they had no data on miR‐146a. Thus, 14 articles met the inclusion criteria: one report contained data on two different groups, so we independently analyzed those studies. These studies consisted of 683 patients and 477 controls (Table , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these were excluded because they had no data on miR‐146a. Thus, 14 articles met the inclusion criteria: one report contained data on two different groups, so we independently analyzed those studies. These studies consisted of 683 patients and 477 controls (Table , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although studies have shown that increased miR‐146a levels are associated with RA, have and identified a correlation between miR‐146a levels and RA activity, other reports have found no such associations . These disparities are probably caused by small sample sizes, low statistical power and/or clinical heterogeneity.…”
Section: Introductionmentioning
confidence: 97%
“…22 Another interesting study indicates that miR-146a discloses a potential predictive value for clinical response to Tripterygium wilfordii Hook F (TwHF) treatment in RA patients. 23 These previous studies suggest that miRNAs have potential value in predicting treatment efficacy in RA patients.…”
Section: Discussionmentioning
confidence: 97%
“…Of the 20 patients, 5 were male and 15 were females, with a mean age of 53 years. All patients with RA were diagnosed according to the standard for the American College of Rheumatology Classification Criteria (22). Normal synovial tissue was obtained from 10 healthy controls (5 male and 5 female patients with a mean age of 38 years) that had undergone amputation between June 2015 and June 2016 in the Orthopedics Department due to accidents but did not have rheumatoid disease.…”
Section: Methodsmentioning
confidence: 99%